2017
DOI: 10.20953/1729-9225-2017-3-25-32
|View full text |Cite
|
Sign up to set email alerts
|

A comparative efficacy and safety of using antiviral drugs in therapy of patients with influenza

Abstract: Цель. Сравнительное изучение клинической эффективности и безопасности применения противовирусных препаратов Триазавирин ® и Тамифлю ® в лечении больных гриппом. Материалы и методы. Всего в исследование были включены 127 пациентов в возрасте от 18 до 65 лет с лабораторно подтвержденным диагнозом «грипп средней степени тяжести». У абсолютного большинства больных (90,6%, n = 114) был диагностирован грипп типа A. Основную группу составили 82 пациента, получавших препарат Триазавирин ® по 1 капсуле (250 мг) 3 раза … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…medication Triazavirin (2-methylsulfanyl-6-nitro [1,2,4]triazolo [5,1-c] [1,2,4]triazin-7-one sodium salt dihydrate) showed a broad spectrum of antiviral action and high efficacy. The medication protects against infection caused by influenza viruses, [6][7][8][9] ARVI, 10 tick-borne encephalitis. 11,12 Triazavirin has been shown to be effective in treating patients with moderate COVID-19.…”
mentioning
confidence: 99%
“…medication Triazavirin (2-methylsulfanyl-6-nitro [1,2,4]triazolo [5,1-c] [1,2,4]triazin-7-one sodium salt dihydrate) showed a broad spectrum of antiviral action and high efficacy. The medication protects against infection caused by influenza viruses, [6][7][8][9] ARVI, 10 tick-borne encephalitis. 11,12 Triazavirin has been shown to be effective in treating patients with moderate COVID-19.…”
mentioning
confidence: 99%
“…A number of research studies, including those of preclinical and clinical trials, have revealed that Triazavirin, which can be considered a guanine analogue, possesses pronounced activity against various strains of influenza virus, including H1N1, H3N2, H5N1, H5N2, H9N2, and H7N3 [ 3 , 4 , 5 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Triazavirin has successfully passed three phases of clinical trials, thus proving its clinical efficacy and safety in the treatment of adult patients with confirmed influenza diagnosis, as indicated in the State Register of Pharmaceutical Products for Medical Purposes of Russian Federation [ 3 , 7 , 9 , 60 ].…”
Section: Pharmacological Properties Of Triazavirinmentioning
confidence: 99%
“…Thus, it was shown that Triazavirin (30 people, 750 mg/day) is comparable to Oseltamivir (29 people, 150 mg/day) in clinical efficacy for the treatment of patients with confirmed influenza diagnosis [ 66 ]. Another comparison, of Triazavirin (82 patients, 750 mg/day for 5 days) with Tamiflu (45 patients, 150 mg/day for 5 days), revealed that the times to recovery and the disappearance of fever, headache, and myalgia were shorter in the patience group administered with Triazavirin [ 63 , 64 , 66 , 67 ].…”
Section: Pharmacological Properties Of Triazavirinmentioning
confidence: 99%
“…On the basis of nitro-containing azoloazinium compounds, employees of Ural Federal University, Institute of Organic Synthesis of the Ural Branch of the Russian Academy of Sciences, and the Research Institute of Influenza of the Ministry of Health of Russia developed a new class of substances -potential drugs with a wide range of antiviral activity [8]. The main representative of this class of compounds is a drug Triazavirin ® (Riamilovir), which is registered in the Russian Federation and successfully used in the treatment of influenza, SARS, COVID-19 [10][11][12][13]. The sodium salt of 3nitro-4-hydroxy-7-methylthio-4H- [1,2,4]triazolo [5,1-c] [1,2,4]triazinide monohydrate (compound 1) is the closest, in structure, compound to the antiviral drug Triazavirin ® and is currently under development as a drug.…”
Section: Introductionmentioning
confidence: 99%